Using telehealth in motor neuron disease to increase access to specialist multidisciplinary care: a UK-based pilot and feasibility study - Susan Mawson; Cindy Cooper; Mike Bradburn; Pamela J Shaw; Esther V Hobson; Wendy O Baird; Ann Quinn; Theresa Walsh (BMJ Open)
Objectives Care of patients with motor neuron disease (MND) in a specialist, multidisciplinary clinic is associated with improved survival, but access is not universal. We wanted to pilot and establish the feasibility of a definitive trial of a novel telehealth system (Telehealth in Motor neuron disease, TiM) in patients with MND.Design An 18-month, single-centre, mixed-methods, randomised, controlled pilot and feasibility study.Intervention TiM telehealth plus usual care versus usual care.Setting A specialist MND care centre in the UK.Participants Patients with MND and their primary informal carers.Primary and secondary outcome measures Recruitment, retention and data collection rates, clinical outcomes including participant quality of life and anxiety and depression.Results Recruitment achieved the target of 40 patients and 37 carers. Participant characteristics reflected those attending the specialist clinic and included those with severe disability and those with limited experience of technology. Retention and data collection was good. Eighty per cent of patients and 82% of carer participants reported outcome measures were completed at 6 months. Using a longitudinal analysis with repeated measures of quality of life (QoL), a sample size of 131 per arm is recommended in a definitive trial. The methods and intervention were acceptable to participants who were highly motivated to participate to research. The low burden of participation and accessibility of the intervention meant barriers to participation were minimal. However, the study highlighted difficulties assessing the associated costs of the intervention, the challenge of recruitment in such a rare disease and the difficulties of producing rigorous evidence of impact in such a complex intervention.Conclusion A definitive trial of TiM is feasible but challenging. The complexity of the intervention and heterogeneity of the patient population means that a randomised controlled trial may not be the best way to evaluate the further development and implementation of the TiM.Trial registration number ISRCTN26675465.